2020
DOI: 10.2147/dmso.s278267
|View full text |Cite
|
Sign up to set email alerts
|

<p>Resveratrol Inhibits Lipopolysaccharide-Induced Extracellular Matrix Accumulation and Inflammation in Rat Glomerular Mesangial Cells by SphK1/S1P2/NF-κB Pathway</p>

Abstract: Chronic inflammation plays a key role in the pathogenesis of various diseases such as diabetic nephropathy (DN). Resveratrol (RSV), a natural polyphenol, has been proven to have renoprotective effects. In this study, we used a lipopolysaccharide (LPS)induced rat glomerular mesangial cells (RMCs) model, to elucidate the renoprotective effect of RSV on sphingosine kinase 1 (SphK1)/sphingosine 1-phosphate receptor 2 (S1P2)/NF-κB activation and the expression of downstream inflammatory mediators, such as intercell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 43 publications
4
11
0
Order By: Relevance
“…All three tested downstream mediators of TLR2 and TLR4, induced nitric oxide synthase (iNOS), phosphorylated extracellular signal-regulated kinase (pERK), and interferon regulatory factor 1 (IRF1), displayed maximal activation (as measured by an increase in protein levels for iNOS and IRF1 and phosphorylation of ERK) 30 min after stimulation, with a decrease 30 min later (Fig. 2 E; representative Western blots shown on the left) as previously described in other cell types [ 41 , 42 ]. These data provided evidence for the responsive and functional nature of TLR2 and TLR4 to LPS by in vitro - expanded WT NPCs derived from mouse neonatal spinal cords.…”
Section: Resultssupporting
confidence: 56%
“…All three tested downstream mediators of TLR2 and TLR4, induced nitric oxide synthase (iNOS), phosphorylated extracellular signal-regulated kinase (pERK), and interferon regulatory factor 1 (IRF1), displayed maximal activation (as measured by an increase in protein levels for iNOS and IRF1 and phosphorylation of ERK) 30 min after stimulation, with a decrease 30 min later (Fig. 2 E; representative Western blots shown on the left) as previously described in other cell types [ 41 , 42 ]. These data provided evidence for the responsive and functional nature of TLR2 and TLR4 to LPS by in vitro - expanded WT NPCs derived from mouse neonatal spinal cords.…”
Section: Resultssupporting
confidence: 56%
“…All three tested downstream mediators of TLR2 and TLR4, induced nitric oxide synthase (iNOS), phosphorylated extracellular signal-regulated kinase (pERK), and interferon regulatory factor 1 (IRF1), displayed maximal activation (as measured by an increase in protein levels for iNOS and IRF1 and phosphorylation of ERK) 30 minutes after stimulation, with a decrease 30 minutes later (Fig. 2E; representative Western blots shown on the left) as previously described in other cell types [40,41]. These data provided evidence for the responsive and functional nature of TLR2 and TLR4 to LPS by in vitro-expanded WT NPCs derived from mouse neonatal spinal cords.…”
Section: Tlr Expression By In Vitro-expanded Npcs Isolated From the Postnatal Mouse Spinal Cordsupporting
confidence: 59%
“…The early stage of DN is mainly characterized by abnormal renal hemodynamics, which mainly manifests as decreased vascular resistance in the glomerulus ( Toledo et al, 2015 ). Research has shown that accumulation of ECM production in the glomerular mesangial membrane may be related to NF-κB pathway ( Gong et al, 2020 ). The ameliorative effects of berberine (300 mg/kg) on ECM accumulation may be due to decreased TGF-β1 and ICAM-1 resulting from inhibition of the NF-κB pathway, as shown in a rat model of DN ( Liu et al, 2010a ).…”
Section: Effects Of Berberine On Vascular Diseasesmentioning
confidence: 99%